2018
DOI: 10.1002/hed.25480
|View full text |Cite
|
Sign up to set email alerts
|

Compartmental surgery for oral tongue and floor of the mouth cancer: Oncologic outcomes

Abstract: Background: Oral tongue/floor of mouth squamous cell carcinoma (OTFMSCC) with a depth of invasion (DOI) > 10 mm involves extrinsic muscles and lingual neurovascular/lymphatic bundles. "Compartmental" hemiglossopelvectomy (CHGP) was developed to improve loco-regional control by "en bloc" removal of tumor and its pathways of spread. Methods: We conducted a retrospective observational study on 45 CHGPs performed at a single institution for OTFMSCC with a DOI > 10 mm at CT/MR. Group A (n = 35) included naïve patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 18 publications
5
39
0
Order By: Relevance
“…T‐N tract involvement was significantly different in the tongue extrinsic muscles infiltrated by disease: we found significantly more patients with T‐N tract disease involvement when the tongue extrinsic muscles were also affected ( P ‐value = .004). In the anterior part of the tongue, infiltration of the extrinsic muscles by disease can be considered as a depth of invasion (DOI) >10 mm . This confirms the idea of the new 8th TNM edition in which cancer with a DOI >of 5 mm has a worse prognosis also with the additional possibility of disease in the T‐N tract…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…T‐N tract involvement was significantly different in the tongue extrinsic muscles infiltrated by disease: we found significantly more patients with T‐N tract disease involvement when the tongue extrinsic muscles were also affected ( P ‐value = .004). In the anterior part of the tongue, infiltration of the extrinsic muscles by disease can be considered as a depth of invasion (DOI) >10 mm . This confirms the idea of the new 8th TNM edition in which cancer with a DOI >of 5 mm has a worse prognosis also with the additional possibility of disease in the T‐N tract…”
Section: Discussionsupporting
confidence: 61%
“…Upon removing the T‐N tract en bloc with the tongue tumor and neck lymph nodes, we removed all the tissues in which the tumor could present a local relapse. Given these observations, CTS with T‐N tract en bloc resection could be considered as a protective procedure for locoregional events …”
Section: Discussionmentioning
confidence: 99%
“…Hence we can assume that when extrinsic muscles are not involved by the tumor, usually for T1-T2 with DOI < 10 mm (3), the lesion can be safely removed transorally. On the other hand, in more advanced stages, the paradigm shift from circumferential and/or cuneiform to longitudinal compartmental resection allows obtaining the best loco-regional control (41,43). DOI, particularly for earlyintermediate lesions (cT1-T2N0), is crucial in deciding whether to perform a simultaneous neck dissection or defer it after formal histopathological evaluation raising the doubt of a higher risk for occult nodal metastasis (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, small cancers (<2 cm), infiltrating in depth more than 5 mm, migrated from T1 to T2. Interestingly, according to Kano et al (10), no significant difference was found between tongue SCC prognostic groups separated by a DOI of 5 mm, while such a distinction proved real when the groups were separated by a DOI of 10 mm, thus reinforcing the anatomical concepts of tongue compartmentalization (5,10,18).…”
Section: Validation?mentioning
confidence: 98%
“…At the same time, clinical DOI assessment should be refined since it is of crucial importance in the treatmentplanning phase. So far it is usually ascertained through clinical examination and imaging, mostly magnetic resonance (MR) (10): measurements of the size and DOI of a given tumor allow to precisely refine clinical staging and thus help in choosing the extent of resection, need for compartmental surgery, possible reconstruction, and/ or neck dissection (18,22). Previous studies, although retrospective, supported the employment of MR in the clinical assessment of DOI (23,24) underlying a good correlation between tumor thickness by MR and histologic DOI, even though imaging usually overestimates the latter, probably due to the coexistence of at least two phenomena: peritumoral edema on one hand, and shrinkage of the specimen after surgical resection and fixation on the other (23,24).…”
Section: Open Questionsmentioning
confidence: 99%